Structural Performance Analysis of Cross-Laminated Timber-Bamboo (CLTB) - Barreto, Maria I. M.; De Araujo, Victor; Cortez-Barbosa, Juliana [UNESP]; Christoforo, Andre L.; Moura, Jorge D. M. (North Carolina State Univ Dept Wood & Paper Sci, 2019)
Construction systems based on cross-laminated timber (CLT) have versatility in material development and are an interesting alternative for construction. This study evaluated the structural performance of cross- laminated timber-bamboo produced from wood (Pinus spp.) and bamboo (Dendrocalamus giganteus). Panels were produced by strips (wood and bamboo) assorted, under non-destructive structural grading, to support a better panel configuration. Small-length pine pieces were also included in the study, considering their low added-value and underutilization in sawmills from Telemaco Borba, Brazil. Gluing tests of small specimens were performed to evaluate the bonding quality of three adhesives: melamine-urea-formaldehyde (MUF), isocyanate polymeric emulsion (IPE), and castor oil-based resin (COR). Shear stress strength parallel to grain between bamboo and wood showed the best performance for MUF resin. After preliminary gluing testing, eight cross-laminated panels were produced with MUF adhesive in a three-layered configuration, with transversal orientation: two external bamboo layers and a central layer of pine wood. Stiffness and rupture strength values were above those specified by the ANSI/APA PGR 320 (2012) standard. Elasticity and rupture moduli were 13,310 MPa and 65 MPa, respectively, showing good potential of this composite for structural uses.
Keywords: Cross-laminated timber-bamboo; Lignocellulosic material; Wood-bamboo construction; Structural panels